Agrikultura ta Paddakal na Danum A Synthesis of Collective Knowledge through a Farmer-Nature Landscape Approach for the Agricity of Ilagan, Isabela - Inere, Moses Aaron B.
Flooding has been part of the landscape of Ilagan due to its geographical location in Cagayan Valley. As a prime agricultural city in the country, Ilagan has experienced considerable damage to its agricultural landscape and is threatened by a production decline because of flooding. Hence, there is a need to devise adaptation measures to sustain the productivity of Ilagan’s farmlands even in the face of flooding. An approach accentuating local knowledge is important to integrate at-risk communities’ adaptation learnings with established risk science for a more effective agricultural flooding response. The study achieved this by conducting a focus group discussion with an Ibanag farming community to explore indigenous agricultural flood adaptation measures. The study revealed four measures namely cultural, environmental sensitivity, temporal, and physical adaptation. This was supplemented by several interviews with agricultural experts and desk research to produce a toolkit of fifteen flood adaptation measures acknowledged by the scientific community. The integration of these knowledge types was tested through the community participatory workshop where local representatives shared their insights regarding agriculture in Ilagan and the proposed toolkit. From here, the study assessed three scenarios based on the pillar of climate-smart agriculture to select the most optimum condition. Finally, a masterplan guided by the four core principles extracted from the Ibanag farmers and strengthened by the fifteen specific agricultural flood adaptation measures was produced and developed into eight typologies. With this, the thesis aimed to contribute to the agricultural sector of Ilagan by proposing a flood-adaptive agricultural landscape plan informed by the integration of local and scientific knowledge.